Cognitive effects of vortioxetine in older adults: a systematic review. (July 2021) - Bishop, Makenna M.; Fixen, Danielle R.; Linnebur, Sunny A.; Pearson, Scott M.
Many older adults experience a deterioration in cognitive function with aging, and this can have a negative impact on quality of life. Late-life depression has been linked to mild cognitive impairment and dementia, and treating depression with an agent that has procognitive effects could be beneficial. Vortioxetine is a novel antidepressant with a multimodal mechanism of action that works primarily via serotonin transporter inhibition, 5-HT1A receptor agonism and 5-HT3 receptor antagonism. A recent systematic review demonstrated procognitive effects of vortioxetine when indirectly compared with selective serotonin reuptake inhibitors and serotonin–norepinephrine reuptake inhibitors in adults aged 18–65 years with major depressive disorder. While this systematic review demonstrated promising procognitive effects from vortioxetine, the included studies did not enroll older adults, who are at the highest risk of cognitive impairment. Therefore, our systematic review sought to investigate the effects of vortioxetine on cognitive functioning in patients over the age of 65 years. Three studies met the prespecified search criteria and were evaluated. Overall, these preliminary data suggest that vortioxetine has promising effects in improving cognition in older adults with depressive symptoms and may have a place in therapy in older adults with depression and/or cognitive impairment, including Alzheimer's disease. Additional long-term studies that include more diverse populations with comorbidities and direct comparisons with other antidepressants are needed to fully understand the potential cognitive benefits in older adults.